CHD2 pathogenic nonsense variant in a three-generation family with variable phenotype and a paracentric inversion 16: Case report - Eleni Angelopoulou; Athina Theodosiou; Ioannis Papaevripidou; Angelos Alexandrou; Thomas Liehr; Yolanda Gyftodimou; Eunice G. Stefanou; Carolina Sismani (Heliyon, 2023)
Chromosomal inversions are usually balanced structural chromosomal rearrangements that do not have an impact on the clinical phenotype of a carrier. The main clinical consequence of inversions is the risk for unbalanced gametes and offspring with severe phenotypes. Rarely though, inversions are associated with a phenotype, mainly due to submicroscopic Copy Number Variants (CNVs) or disruption at the breakpoints of a functionally important gene and/or genomic elements. In this study, a paracentric inversion of chromosome 16 [inv(16)(q22.3q24.1)] was identified in a three-generation family with discordant phenotypes with/without epilepsy and/or intellectual impairment, as well as with an unaffected carrier. This finding was confirmed by fluorescence in situ hybridization (FISH). Genetic investigation, initially with chromosomal microarray (CMA), did not reveal any copy number variants. Finally, Clinical Exome Sequencing (CES), detected the presence of a pathogenic nonsense variant (rs797044912) in the Chromodomain Helicase DNA-binding protein 2 (CHD2) gene [NM_001271.4:c.5035C>T p.(Arg1679Ter)]. CHD2 pathogenic variants have been associated with Developmental and Epileptic Encephalopathy-94 (DEE-94), a rare yet severe condition, characterized by developmental delay, seizures with an early onset, intellectual impairment, autism spectrum disorder, and sometimes behavioral issues. Family testing showed that the variant segregated with phenotypic heterogeneity in the affected individuals and appears to be causative. To the best of our knowledge, this is the first CHD2 pathogenic variant segregating in a three-generation family and the fourth familial case reported. These results further support our previous findings that familial, balanced rearrangements with discordant phenotypes in the same family are, in the vast majority, coincidental.